Isotopic Signatures of Methane Emissions From Dairy Farms in California's San Joaquin Valley. Issue 1 (24th January 2022) - Carranza, Valerie; Biggs, Brenna; Meyer, Deanne; Townsend‐Small, Amy; Thiruvenkatachari, Ranga Rajan; Venkatram, Akula; Fischer, Marc L.; Hopkins, Francesca M.
Abstract: In this study, we present seasonal atmospheric measurements of δ 13 CCH4 from dairy farms in the San Joaquin Valley of California. We used δ 13 CCH4 to characterize emissions from enteric fermentation by measuring downwind of cattle housing (e.g., freestall barns, corrals) and from manure management areas (e.g., anaerobic manure lagoons) with a mobile platform equipped with cavity ring‐down spectrometers. Across seasons, the δ 13 CCH4 from enteric fermentation source areas ranged from −69.7 ± 0.6 per mil (‰) to −51.6 ± 0.1‰ while the δ 13 CCH4 from manure lagoons ranged from −49.5 ± 0.1‰ to −40.5 ± 0.2‰. Measurements of δ 13 CCH4 of enteric CH4 suggest a greater than 10‰ difference between cattle production groups in accordance with diet. Isotopic signatures of CH4 were used to characterize enteric and manure CH4 from downwind plume sampling of dairies. Our findings show that δ 13 CCH4 measurements could improve the attribution of CH4 emissions from dairy sources at scales ranging from individual facilities to regions and help constrain the relative contributions from these different sources of emissions to the CH4 budget. Plain Language Summary: Methane emissions from livestock production are an important part of the global methane budget. However, more measurements of carbon isotopes of methane are needed to help constrain the relative contribution of methane sources regionally. In this study, we measured carbon isotopes of methane at dairy farms in California, the leading dairy‐producing state in the United States. Different areas of the dairy farm had distinct methane generation processes, reflected in the isotopic signatures of methane that were emitted. Methane from manure lagoons was more enriched in the heavier of carbon's two stable isotopes, carbon‐13, than methane from enteric fermentation across seasons at a dairy farm. Isotopic signatures of methane were comparable across seasons, particularly from manure lagoons. In addition, enteric methane from different cattle production groups had distinct isotopic signatures of methane that are likely dependent on diet composition. Isotopic signatures can also be used to apportion methane emissions from both enteric fermentation and anaerobic manure lagoons by taking samples downwind of dairy farms. This can help constrain the relative contributions from these different sources of emissions to the methane budget, as well as track the effectiveness of mitigation strategies by estimating the contribution of sources. Key Points: Stable carbon isotopic signatures of methane emitted from manure lagoons were more enriched than methane from enteric fermentation Downwind plume sampling of stable carbon isotopic signatures of methane can be used to characterize enteric and manure methane Isotopic signatures of methane varied between different cattle production groups in accordance with diet